Method for preparing seawater sea sand recycled concrete beam reinforced by FRP (Fiber Reinforce Plastic) ribs through CO2 curing
The preparation method of enhanced seawater and sea sand recycled concrete beams through CO2 curing FRP ribs is solved, and the problem of low carbonized concrete value is easily corroded, and the high durability and compressive strength of concrete is achieved. It is suitable for the carbonization of large-sized specimens and precast concrete. It is suitable for the carbonization of large-sized specimens and precast concrete. Maintenance.
Patent Information
- Application Number
- CN202411696923.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-26
AI Technical Summary
In the prior art, the carbonized concrete value is low and the carbonization curing process of large-size specimens and precast concrete is insufficient, which affects the durability of the fiber-reinforced concrete structure.
The preparation method of seawater and sea sand recycled concrete beams is used to enhance the CO2 curing FRP ribs. The seawater and sea sand recycled concrete are made by mixing recycled aggregate, sea sand, artificial simulated seawater, water reducer and cement, and industrial waste is introduced into the confined space. The carbon dioxide gas is carbonized and cured, and carbonization channels are reserved to quickly carbonize concrete.
It improves the durability of concrete, enhances compressive strength, solves the problem of chloride ion erosion in seawater and sea sand recycled concrete, and shortens the maintenance age.
Smart Images

Figure CN119388553A_ABST
Abstract
Description
Technical field:
[0001] The present invention relates to the technical field of maintenance of precast concrete components, and in particular to a method of using CO 2 A preparation method for curing FRP bars reinforced with seawater and sea sand recycled concrete beams. Background technology:
[0002] Concrete structure is the most important structure in civil engineering. It will emit a large amount of CO2 during the production, transportation and concrete preparation of raw materials. CO2 is one of the main greenhouse gases. It is of great significance to find a method for making concrete structure that can effectively save energy and reduce emissions.
[0003] Carbon dioxide curing of concrete is one of the promising methods and is of great help in achieving carbon neutrality. However, there are certain limitations in the research on carbon dioxide in cementitious materials. The application experiments of carbon dioxide curing concrete are mostly concentrated on small-sized specimens such as blocks, and there is a lack of experiments on large-sized specimens, especially research on the carbonation curing process of large precast concrete.
[0004] The large-scale growth of the construction industry has generated a large amount of construction and demolition waste. Recycling waste concrete as a renewable resource and using it in new projects is an effective way to improve the resource utilization of construction solid waste. Due to the accumulation of internal damage in the waste concrete during the crushing process, the aggregates accumulate under the action of external forces, resulting in many microcracks, and serious loss of particle size and strength; in addition, the loose and porous hardened cement mortar attached to the surface of the recycled aggregate causes the quality of the recycled aggregate to be lower than that of the natural aggregate.
[0005] Current research progress shows that the carbonation depth of carbonization-enhanced concrete is generally low, which affects the improvement of the durability of fiber-reinforced composite (FRP) reinforced concrete structures. Summary of the invention:
[0006] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a method for preparing seawater and sea sand recycled concrete beams reinforced with FRP bars using CO2 for curing. The method for preparing seawater and sea sand recycled concrete beams reinforced with FRP bars using CO2 for curing is beneficial to solving the defects of low carbonization value of concrete and easy corrosion of steel bars.
[0007] The present invention provides a method for preparing seawater and sea sand recycled concrete beams by using CO2 to cure FRP bars, which is characterized by: the specific process includes:
[0008] (1) Mix recycled aggregate, sea sand, artificial simulated sea water, water reducing agent and cement to produce sea water and sea sand recycled concrete;
[0009] (2) Install the bottom template;
[0010] (3) Lay FRP bars and install casing for forming the hole;
[0011] (4) Install the side formwork;
[0012] (5) Pour the stirred seawater and sea sand recycled concrete into the mold, wait until the concrete pouring is completed to form a test block, and then send the test block to the curing room for standard curing;
[0013] (6) After the expected standard curing time is reached, the casing is pulled out from the test block to expose the pores required for concrete carbonization near the FRP bars;
[0014] (7) The test block is then sent to a carbon dioxide curing box for curing. In a closed space, a pressurized air pump is set up on both sides of the reserved channel to introduce industrial waste carbon dioxide gas into the reserved channel for carbonization curing;
[0015] (8) When the curing time reaches the expected carbonization depth, take out the test block;
[0016] (9) Finally, grouting is performed to fill the reserved holes.
[0017] The present invention provides a method for preparing seawater and sea sand recycled concrete beams by using CO2 to cure FRP bars, which is characterized by: the specific process includes:
[0018] (1) Mix recycled aggregate, sea sand, artificial simulated sea water, water reducing agent and cement to produce sea water and sea sand recycled concrete;
[0019] (2) Install the bottom template;
[0020] (3) Lay FRP bars and set up rectangular prefabricated molds;
[0021] (4) Install the side formwork;
[0022] (5) Pour the stirred seawater and sea sand recycled concrete into the mold, wait until the concrete pouring is completed to form a test block, and then send the test block to the curing room for standard curing;
[0023] (6) After the expected standard curing time is reached, the prefabricated cube mold is pulled out to expose the area near the steel bars required for concrete carbonization;
[0024] (7) The test block is then sent to a carbon dioxide curing box for curing, and industrial waste carbon dioxide gas is introduced into the closed space for carbonization curing;
[0025] (8) When the curing time reaches the expected carbonization depth, take out the test block;
[0026] (9) Finally, grouting is performed to fill the reserved area.
[0027] Preferably, the FRP bars include one or more of basalt fiber reinforced composite bars (BFRP), glass fiber reinforced composite bars (GFRP), and carbon fiber reinforced composite bars (CFRP).
[0028] Preferably, the water is artificial simulated seawater.
[0029] Preferably, the above-mentioned sea sand can be replaced by one or more of regenerated sand, river sand and shell sand.
[0030] Preferably, the mixed recycled aggregate includes construction waste and industrial carbon dioxide waste gas that are recycled from building crushing.
[0031] The concrete cured by carbon dioxide in the preparation method of the present invention can not only store fixed carbon dioxide gas, but also has a very dense microstructure, so that it has good durability (corrosion resistance, permeability resistance, and freeze-thaw cycle resistance) that general concrete does not have. Fiber-reinforced composite materials (FRP) have the advantages of high strength, light weight, and good corrosion resistance, and can be directly applied to seawater and sea sand concrete instead of steel as a reinforcing material; the combination of the two materials perfectly solves the defect of easy corrosion of steel bars due to the use of seawater and sea sand; in addition, the presence of recycled aggregates can improve the curing efficiency of carbon dioxide and significantly enhance the compressive strength of recycled concrete due to their high porosity.
[0032] This method reserves a carbonization channel in advance when making beams, creates conditions for rapid carbonization of the concrete around the steel bars, and allows the concrete near the steel bars to fully contact carbon dioxide during the carbonization process, so that the concrete near the FRP bars is quickly carbonized. This can not only improve the early strength of precast concrete beams and shorten the curing age, but also combine FRP bars and seawater and sea sand recycled concrete well, solve the chloride ion erosion in seawater and sea sand recycled concrete, and solve the long-term performance degradation of FRP steel bars caused by high concrete pH value. Description of the drawings:
[0033] Figure 1 is a schematic diagram of the cross-section of a beam manufactured by the first method of the present invention;
[0034] In the figure, 1 refers to the hole, 2 refers to the FRP bar, 3 refers to the distance between the hole and the FRP bar, and 4 refers to the concrete area;
[0035] Figure 2 is a schematic diagram of the cross-section of a beam manufactured by the second method of the present invention;
[0036] In the figure, 1 refers to the opening area, 2 refers to the concrete area, 3 refers to the FRP reinforcement, and 4 refers to the longitudinal distance of the square hole;
[0037] Figure 3is a schematic diagram of the cross-section structure of a beam according to a first embodiment of the present invention;
[0038] Figure 4 This is a schematic diagram of the carbonization degree of concrete around the steel bars after curing is completed in the first embodiment;
[0039] Figure 5 is a schematic diagram of the cross-section structure of a beam according to a second embodiment of the present invention;
[0040] Figure 6 is a schematic diagram of the height of the compression zone;
[0041] Figure 7 is a schematic diagram of specific dimensions of a cross section of a beam in a second embodiment of the present invention;
[0042] Figure 8 It is a schematic diagram of the carbonization degree of concrete around the steel bars after curing is completed in the second embodiment. Specific implementation method:
[0043] The first method of preparing seawater and sea sand recycled concrete beams by using CO2 to cure FRP bars is characterized in that the specific process includes:
[0044] (1) Mix recycled aggregate, sea sand, artificial simulated sea water, water reducing agent and cement to produce sea water and sea sand recycled concrete;
[0045] (2) Install the bottom template;
[0046] (3) Lay FRP bars and install casing for forming the hole;
[0047] (4) Install the side formwork;
[0048] (5) Pour the stirred seawater and sea sand recycled concrete into the mold, wait until the concrete pouring is completed to form a test block, and then send the test block to the curing room for standard curing;
[0049] (6) After the expected standard curing time is reached, the casing is pulled out from the test block to expose the pores required for concrete carbonization near the FRP bars;
[0050] (7) The test block is then sent to a carbon dioxide curing box for curing. In a closed space, a pressurized air pump is set up on both sides of the reserved channel to introduce industrial waste carbon dioxide gas into the reserved channel for carbonization curing;
[0051] (8) When the curing time reaches the expected carbonization depth, take out the test block;
[0052] (9) Finally, grouting is performed to fill the reserved holes.
[0053] The second method of preparing seawater and sea sand recycled concrete beams reinforced with CO2-cured FRP bars is characterized in that the specific process includes:
[0054] (1) Mix recycled aggregate, sea sand, artificial simulated sea water, water reducing agent and cement to produce sea water and sea sand recycled concrete;
[0055] (2) Install the bottom template;
[0056] (3) Lay FRP bars and set up cube prefabricated molds;
[0057] (4) Install the side formwork;
[0058] (5) Pour the stirred seawater and sea sand recycled concrete into the mold, wait until the concrete pouring is completed to form a test block, and then send the test block to the curing room for standard curing;
[0059] (6) After the expected standard curing time is reached, the prefabricated cube mold is pulled out to expose the area near the steel bars required for concrete carbonization;
[0060] (7) The test block is then sent to a carbon dioxide curing box for curing, and industrial waste carbon dioxide gas is introduced into the closed space for carbonization curing;
[0061] (8) When the curing time reaches the expected carbonization depth, take out the test block;
[0062] (9) Finally, grouting is performed to fill the reserved area.
[0063] The above-mentioned FRP bars include one or more of basalt fiber reinforced composite bars (BFRP), glass fiber reinforced composite bars (GFRP), and carbon fiber reinforced composite bars (CFRP); the above-mentioned water is artificial simulated seawater; the above-mentioned sea sand can be replaced by one or more of recycled sand, river sand, and shell sand; the above-mentioned mixed recycled aggregate includes construction waste recycled from building crushing and industrial carbon dioxide waste gas.
[0064] The concrete cured by carbon dioxide in the preparation method of the present invention can not only store fixed carbon dioxide gas, but also has a very dense microstructure, so that it has good durability (corrosion resistance, permeability resistance, and freeze-thaw cycle resistance) that general concrete does not have. Fiber-reinforced composite materials (FRP) have the advantages of high strength, light weight, and good corrosion resistance, and can be directly applied to seawater and sea sand concrete instead of steel as a reinforcing material; the combination of the two materials perfectly solves the defect of easy corrosion of steel bars due to the use of seawater and sea sand; in addition, the presence of recycled aggregates can improve the curing efficiency of carbon dioxide and significantly enhance the compressive strength of recycled concrete due to their high porosity.
[0065] This method reserves a carbonization channel in advance when making beams, creates conditions for rapid carbonization of the concrete around the steel bars, and allows the concrete near the steel bars to fully contact carbon dioxide during the carbonization process, so that the concrete near the FRP bars is quickly carbonized. This can not only improve the early strength of precast concrete beams and shorten the curing age, but also combine FRP bars and seawater and sea sand recycled concrete well, solve the chloride ion erosion in seawater and sea sand recycled concrete, and solve the long-term performance degradation of FRP steel bars caused by high concrete pH value.
[0066] Embodiment of the first method of the present invention:
[0067] The materials used are 42.5 grade ordinary Portland cement, artificial simulated seawater, sea sand and other raw materials, the water-cement ratio is 0.47, and the environmental category is Class I.
[0068] SSRAC concrete mix ratio
[0069]
[0070] Concrete is prepared according to the mix ratio of concrete in the table and mixed by dry mixing method. First, dry mix cement, aggregate and fine aggregate for 90 seconds to ensure uniform mixing. Then add 90% of mixing water into the mixer and stir for about 90 seconds. Then add 10% of mixing water and water reducing agent and stir for 90 seconds before pouring into the mold.
[0071] According to the principle of concrete cover thickness, the minimum distance between the hole and the FRP reinforcement is limited to ensure the bonding between concrete and steel bars. According to the specification, under normal indoor environment, the minimum concrete cover thickness of the beam is 20mm, and 20mm is set as the minimum distance between the hole and the FRP reinforcement.
[0072] In the Chinese building standard "Code for Design of Ordinary Concrete Structures" (GB 50010-2010), it is stipulated that the minimum diameter of embedded pipes in concrete structures should not be less than 20mm, and the hole diameter is taken as 20mm.
[0073] The beam size is 200mm×300mm. The steel bar is GFRP bar with a diameter of 14mm. d is greater than 20mm
[0074] The main forms are Figure 3 As shown in the figure, 3D20@40 is 3 holes with a diameter of 20mm and a spacing of 40mm; 4G14@40 is 4 GFRP bars with a diameter of 14mm.
[0075] The carbonation depth model is used to calculate the carbonation depth of seawater and sea sand recycled concrete. The influence coefficient of this variable can be obtained by analyzing the carbonation depth using the verified seawater and sea sand recycled concrete carbonization model.
[0076] The specific model is as follows:
[0077]
[0078] Where: k W / C —Water-cement ratio influence coefficient; k SS —Influence coefficient of fine aggregate type; m—constant reflecting other factors; T—temperature; C 0 —CO2 concentration; RH—humidity; W / C—water-cement ratio; t—carbonization time (d); t c —Standard curing time (d); f cu —Standard compressive strength; it is known that the standard compressive strength value obtained after standard curing is 34.302Mpa.
[0079] Basic parameters
[0080] Set the curing temperature (T) to 20 degrees; humidity (RH) to 70%; carbon dioxide concentration (C 0 )50%; sea sand water absorption rate 4.69%; water-binder ratio 0.47; after 7 days of standard curing, it is sent to carbonization curing for 21 days; the above parameters are put into the calculation
[0081]
[0082] The carbonization depth can reach 36mm. At this carbonization depth, the concrete around the FRP bars can be completely carbonized. After curing, the carbonization degree of the concrete around the steel bars is about Figure 4 As shown, the gray area is the carbonization completion area; this method is more efficient than the ordinary carbonization curing method; the carbonization of concrete near the steel bars is completed in a shorter standard curing plus carbonization curing time.
[0083] The second method embodiment of the present invention:
[0084] The material is 42.5 grade ordinary Portland cement, artificial simulated seawater, sea sand and other raw materials, with a water-cement ratio of 0.47. The environmental category is Class I.
[0085] SSRAC concrete mix ratio
[0086] Concrete is prepared according to the mix ratio of concrete in the table and mixed by dry mixing method. First, dry mix cement, aggregate and fine aggregate for 90 seconds to ensure uniform mixing. Then add 90% of mixing water into the mixer and stir for about 90 seconds. Then add 10% of mixing water and water reducing agent and stir for 90 seconds before pouring into the mold.
[0087] According to the thickness of the concrete beam protective layer, the minimum distance between the hole and the FRP reinforcement is limited to ensure the bonding between the concrete and the reinforcement. According to the specification, under normal indoor conditions, the minimum concrete protective layer thickness of the beam is 20mm, and 20mm is set as the minimum distance between the hole and the reinforcement.
[0088] The concrete height of the compression zone of the concrete beam when it is bent is determined according to the limit D1, and the size of the beam is 200mm×300mm. The steel bar is GFRP bar with a diameter of 14mm; the main forms are as follows Figure 5 shown.
[0089] (1) Consider D1 size
[0090] The purpose of this calculation is to measure the height x of the compression zone. c (like Figure 6 (shown)
[0091] According to the Concrete Design Principles Code:
[0092] α 1 f c bx=f y A s
[0093] x=2(1-0.6)x c =0.8x c
[0094] β 1 =2(1-k 2 )
[0095] Where: C50 or less α 1 Take 1.0, β 1 Take 0.8. c -Design value of concrete axial compressive strength, f y - Design value of steel bar tensile strength, A s -Area of longitudinal reinforcement. b-Width of beam cross section 200mm. x-Height of compression zone of equivalent rectangular stress diagram, x c - Actual height of the compression zone. The compressive strength of the seawater sand recycled concrete cube cast in this experiment is 34.302Mpa, which belongs to the C30 strength grade concrete. c Take 14.3N / mm 2 The selected reinforcement is 14mm GFRP reinforcement, f y Take 400N / mm 2 , b is 200mm;
[0096] Bring in β 1 =0.8 to obtain
[0097] k 2 =1-0.4=0.6
[0098] x=2(1-0.6)x c =0.8x c
[0099] Bring in f c 、f y , b, α 1 , A s
[0100] α 1 f c bx=f y A s
[0101] 1.0×14.3×200×x=400×4×π×7 2
[0102] x=86.12mm
[0103] x c =86.12 / 0.8=107.65mm
[0104] Note: The distance from the top of the opening to the top of the concrete beam is limited to 107.65 mm.
[0105] The figure shows the size limit of D1. The upper limit is 107.65≈108mm, the lower limit is 25mm for the thickness of the protective layer plus 14mm for the diameter of the steel bar plus 20mm for the thickness of the hole to the steel bar, which is 59mm. The specific size is as follows Figure 7 shown.
[0106] (2) Consider carbonization depth
[0107] 1. Set the curing temperature (T) to 20 degrees;
[0108] 2. Humidity (RH) 70%;
[0109] 3. Carbon dioxide concentration (C 0 )50%;
[0110] 4. The water absorption rate of sea sand is 4.69%;
[0111] 5. Water-cement ratio 0.47;
[0112] 6. After 7 days of standard curing, send to carbonization curing for 21 days;
[0113] The above parameters are brought into the calculation
[0114]
[0115] The carbonization depth can reach 36mm. The carbonization effect is shown in the figure below. The gray area is the carbonization completed area.
[0116] like Figure 8 shown.
[0117] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A method for preparing seawater and sea sand recycled concrete beams by using CO2 to cure FRP bars, characterized in that: The specific process includes: (1) Mix recycled aggregate, sea sand, artificial simulated sea water, water reducing agent and cement to produce sea water and sea sand recycled concrete; (2) Install the bottom template; (3) Lay FRP bars and install casing for forming the hole; (4) Install the side formwork; (5) Pour the stirred seawater and sea sand recycled concrete into the mold, wait until the concrete pouring is completed to form a test block, and then send the test block to the curing room for standard curing; (6) After the expected standard curing time is reached, the installed casing is pulled out from the test block to expose the channels required for concrete carbonization near the FRP bars; (7) The test block is then sent to a carbon dioxide curing box for curing. In a closed space, a pressurized air pump is set up on both sides of the reserved channel to introduce industrial waste carbon dioxide gas into the reserved channel for carbonization curing; (8) When the curing time reaches the expected carbonization depth, take out the test block; (9) Finally, grouting is performed to fill the reserved holes.
2. A method for preparing seawater and sea sand recycled concrete beams by using CO2 to cure FRP bars, characterized in that: The specific process includes: (1) Mix recycled aggregate, sea sand, artificial simulated sea water, water reducing agent and cement to produce sea water and sea sand recycled concrete; (2) Install the bottom template; (3) Lay FRP bars and set up rectangular prefabricated molds; (4) Install the side formwork; (5) Pour the stirred seawater and sea sand recycled concrete into the mold, wait until the concrete pouring is completed to form a test block, and then send the test block to the curing room for standard curing; (6) After the expected standard curing time is reached, the prefabricated rectangular parallelepiped mold is pulled out to expose the area near the steel bars required for concrete carbonization; (7) The test block is then sent to a carbon dioxide curing box for curing, and industrial waste carbon dioxide gas is introduced into the closed space for carbonization curing; (8) When the curing time reaches the expected carbonization depth, take out the test block; (9) Finally, grouting is performed to fill the reserved area.
3. The method for preparing seawater and sea sand recycled concrete beams reinforced with CO2-cured FRP bars according to claim 1 or 2, characterized in that: The FRP bars include one or more of basalt fiber reinforced composite bars (BFRP), glass fiber reinforced composite bars (GFRP), and carbon fiber reinforced composite bars (CFRP).
4. The method for preparing seawater and sea sand recycled concrete beams reinforced with CO2-cured FRP bars according to claim 1 or 2, characterized in that: The water is artificial simulated seawater.
5. The method for preparing seawater and sea sand recycled concrete beams reinforced with CO2-cured FRP bars according to claim 1 or 2, characterized in that: The sea sand can be replaced by one or more of regenerated sand, river sand and shell sand.
6. The method for preparing seawater and sea sand recycled concrete beams reinforced with CO2-cured FRP bars according to claim 1 or 2, characterized in that: The mixed recycled aggregate includes construction wastes and industrial carbon dioxide waste gas that are recycled from broken buildings.
7. The method for preparing seawater and sea sand recycled concrete beams reinforced with CO2-cured FRP bars according to claim 1 or 2, characterized in that: The materials used are 42.5 grade ordinary Portland cement, artificial simulated seawater, sea sand raw materials, and a water-cement ratio of 0.47; SSRAC concrete mix ratio Concrete is prepared according to the concrete mix ratio in the table and mixed by dry mixing method. First, dry mix cement, aggregate and fine aggregate for 90 seconds to ensure uniform mixing. Then add 90% of mixing water into the mixer and stir for about 90 seconds. Then add 10% of mixing water and water reducing agent and stir for 90 seconds before pouring into the mold. According to the thickness of the concrete cover, the minimum distance between the hole and the FRP bar is limited to ensure the bonding between the concrete and the steel bar. The minimum distance between the hole and the FRP bar is set to 20mm, and the hole diameter is 20mm. The size of the beam is 200mm×300mm, and the steel bar is GFRP bar with a diameter of 14mm, and d is greater than 20mm. Use this carbonation depth model to calculate the carbonation depth of seawater and sea sand recycled concrete. Use the verified seawater and sea sand recycled concrete carbonation model to analyze the carbonation depth and obtain the influence coefficient of this variable. The specific model is as follows: Where: X c is the carbonization depth (mm); k W / C —Water-cement ratio influence coefficient; k SS —Influence coefficient of fine aggregate type; m—constant reflecting other factors; T—temperature; C0—carbon dioxide concentration (%); RH—humidity (%); Among them, C RCA , C SS , C BS and C RFA are the amounts of RCA, sea sand, shell sand and reclaimed sand; WA RCA , W.A. SS , W.A. BS and WA RFA is the corresponding water absorption rate (%); W / C—water-to-binder ratio; t—carbonization time (d); t c —Standard curing time (d); f cu —Standard compressive strength; the standard compressive strength after standard curing is known to be 34.302Mpa; Basic parameters: set the curing temperature (T) to 20 degrees; humidity (RH) to 70%; carbon dioxide concentration (C0) to 50%; sea sand water absorption rate to 4.69%; Water-binder ratio is 0.47; after 7 days of standard curing, it is sent to carbonization curing for 21 days; The above parameters are brought into the calculation The carbonization depth can reach 36mm; at this carbonization depth, the concrete around the FRP bars can be completely carbonized.
8. The method for preparing seawater and sea sand recycled concrete beams reinforced with CO2-cured FRP bars according to claim 1 or 2, characterized in that: The materials used are 42.5 grade ordinary Portland cement, artificial simulated seawater, sea sand raw materials, and a water-cement ratio of 0.47; Concrete is prepared according to the concrete mix ratio in the table and mixed by dry mixing method. First, dry mix cement, aggregate and fine aggregate for 90 seconds to ensure uniform mixing. Then add 90% of mixing water into the mixer and stir for about 90 seconds. Then add 10% of mixing water and water reducing agent and stir for 90 seconds before pouring into the mold. According to the thickness of the concrete beam cover, the minimum distance between the hole and the FRP bar is limited to ensure the bonding between the concrete and the steel bar. The minimum distance between the hole and the steel bar is set to 20mm. The size of the beam is 200mm×300mm, and the steel bar uses GFRP bars with a diameter of 14mm. (1) Considering the size of D1, the height x of the compression zone is calculated for the purpose of calculation. c According to the Concrete Design Principles Code: α1f c bx=f y A s x=2(1-0.6)x c =0.8x c β1=2(1-k2) Where: below C50, α1 is 1.0, β1 is 0.8; f c -Design value of concrete axial compressive strength, f y - Design value of steel bar tensile strength, A s - longitudinal reinforcement area. b- beam cross-sectional width 200mm; x- equivalent rectangular stress diagram compression zone height, x c - Actual height of the compression zone. The compressive strength of the seawater sand recycled concrete cube cast in this experiment is 34.302Mpa, which belongs to the C30 strength grade concrete. c Take 14.3N / mm 2 ; The selected reinforcement is 14mm GFRP reinforcement, f y Take 400N / mm 2 , b is 200mm; Substituting β1 = 0.8, we can obtain k2=1-0.4=0.6 x=2(1-0.6)x c =0.8x c Bring in f c 、f y , b, α1, A s α1f c bx=f y A s 1.0×14.3×200×x=400×4×π×7 2 x=86.12mm x c =86.12 / 0.8=107.65mm It indicates that the distance from the top of the opening to the top of the concrete beam is limited to 107.65 mm; The upper limit is 107.65≈108mm, the lower limit is 25mm for the protective layer thickness plus the steel bar diameter of 14mm plus the hole to the steel bar limit thickness of 20mm, which is 59mm. (2) Consider carbonization depth 1. Set the curing temperature (T) to 20 degrees; 2. Humidity (RH) 70%; 3. Carbon dioxide concentration (C0) 50%; 4. The water absorption rate of sea sand is 4.69%; 5. Water-cement ratio 0.47; 6. After 7 days of standard curing, send to carbonization curing for 21 days; The above parameters are brought into the calculation The carbonization depth can reach 36mm. The carbonization effect is shown in the figure below. The gray area is the carbonization completed area.
Citation Information
Patent Citations
Method for preparing fixed carbon concrete prefabricated part by utilizing waste concrete
CN108714962A
Seawater and sea sand concrete and FRP rib long-term cooperative work method considering CO2 curing
CN113021617A
Preparation method of rapidly carbonized seawater sea sand concrete
CN115259780A
Preparation and maintenance method of low-carbon recycled concrete prefabricated part
CN117962095A
Method and structure for reinforcing opening of concrete beam
JP2008031821A
Cited By
Method for curing cement concrete product through CO2 reverse carbonization
CN119330748A